Auditoría en seguridad vial, Armenia Pereira, Tramo Km 21 + 600 al Km 27 + 600 (2023)
The purpose of performing a road safety audit (RSA) allows us to make an accurate diagnosis of the real state of a road, which makes it possible to point out the weaknesses of the designs, the lack of signals or the absence of these on some routes, this could have a decisive impact on the reduction of accidents on the roads of all societies.